2015
DOI: 10.4236/ijamsc.2015.33007
|View full text |Cite
|
Sign up to set email alerts
|

GC/MS: A Valid Tool for Soil Gas Hydrocarbons Speciation

Abstract: This work describes an alternative method based on GC/MS technique with SCAN-ion approach for speciation of hydrocarbons contained in soil gas matrices and sampled on solid sorbent tubes (coconut shell charcoal).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…The GC/MS method previously developed by the authors [13] showed criticisms that are properly investigated in the present work. Moreover, important advances are also reported.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…The GC/MS method previously developed by the authors [13] showed criticisms that are properly investigated in the present work. Moreover, important advances are also reported.…”
Section: Resultsmentioning
confidence: 89%
“…The new method was based on the extraction of more representative ions (ions extraction, IE) of the aliphatic components from TIAC [13].…”
Section: Methods Improvementmentioning
confidence: 99%
See 3 more Smart Citations